Ethical governance of artificial intelligence in the public sector - Ireni Saban, Liza; Sherman, Maya (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book argues that ethical evaluation of AI should be an integral part of public service ethics and that an effective normative framework is needed to provide ethical principles and evaluation for decision-making in the public sphere, at both local and international levels. It introduces how the tenets of prudential rationality ethics through critical engagement with intersectionality can contribute to a more successful negotiation of the challenges created by AI technological innovations and afford a relational, interactive, flexible, and fluid framework that meets the features of AI research projects, so that core public and individual values are still honoured in the face of technological development. This book will be of key interest to scholars, students and professionals engaged in public management and ethics management, AI ethics, public organizations, public service leadership, compliance and more broadly to public administration and policy, applied ethics and philosophy"--
Note -- References -- 5 Contemporary Analysis of AI Affairs in the International Arena -- Cultural Perspectives of Surveillance and Facial Recognition Technologies -- Influence Operations and AI Threats to the Democratic Ethos -- AI-driven Disinformation 2.0 -- Deepfake -- Between AI Technologies and the COVID-19 Pandemic -- Critical Approach to AI Governance in the Public Sector -- References -- Index
"Routledge Focus" -- Cover.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Moral and ethical aspects; Artificial intelligence -- Government policy; POLITICAL SCIENCE / Public Affairs & Administration